Polyarticular psoriatic arthritis is more like oligoarticular psoriatic arthritis, than rheumatoid arthritis. Issue 1 (13th July 2006) - Helliwell, P S; Porter, G; Taylor, W J
Abstract : Background and objective: Since the original description of psoriatic arthritis (PsA) subgroups by Moll and Wright, there has been some discrepancy in the precise prevalence of the different subgroups and in particular the proportion of patients with polyarthritis. The higher prevalence of the polyarthritis subgroup may be due to the inclusion of patients with seronegative rheumatoid arthritis with coincidental psoriasis. The classification of psoriatic arthritis (CASPAR) study database provided an opportunity to examine this question. Methods: The CASPAR study collected clinical, radiological and laboratory data on 588 patients with physician-diagnosed PsA and 525 controls with other inflammatory arthritis, 70% of whom had rheumatoid arthritis. Patients with PsA were divided into two groups: polyarthritis and non-polyarthritis (which included the Moll and Wright subgroups of spinal disease, distal interphalangeal predominant and arthritis mutilans) and were compared with patients with rheumatoid arthritis. Comparisons were made between all three groups and, if a significant difference occurred, between the two groups with PsA. Results: The three groups differed significantly with regard to all clinical and laboratory variables except duration of disease. Significant differences were also found between the two groups of PsA in terms of age, sex, total number of involved joints, disability score and symmetry. However, no differences were found between the groups of patients with PsA in terms of seropositivity for rheumatoid factor and antibodies to cyclic citrullinated peptide, enthesitis, and spinal pain and stiffness. Further, dactylitis was commonly seen in patients with PsA (57% in the polyarticular group and 45% in non-polyarticular group), and uncommonly found in patients with rheumatoid arthritis (5%). With the exception of entheseal changes, syndesmophytes and osteolysis, typical radiological features of PsA could not be used to distinguish between the PsA subgroups. Conclusions: The evidence suggests that the changing prevalence of the polyarticular subgroup of PsA is not because doctors include patients with seronegative rheumatoid arthritis with coincidental psoriasis.